2017
DOI: 10.1016/j.virol.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic response of the insect vector, Peregrinus maidis, to Maize mosaic rhabdovirus and identification of conserved responses to propagative viruses in hopper vectors

Abstract: Maize mosaic virus (MMV) is a plant-pathogenic rhabdovirus that is transmitted by the corn planthopper, Peregrinus maidis, in a propagative manner. P. maidis supports long-term MMV infections with no negative effects on insect performance. To elucidate whole-body transcriptome responses to virus infection, RNA-Seq was used to examine differential gene expression of virus-infected adult insects, and libraries were prepared from replicated groups of virus-exposed insects and non-exposed insects. From the 68,003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 55 publications
5
32
0
Order By: Relevance
“…5 for bumblebee EVEs), suggesting that integrations might have occured due to non-homologous recombination between an RNA of the progenitor virus and that of a retrotransposon during reverse transcription of the retrotransposon (Ballinger et al, 2012;Geuking et al, 2009;Horie et al, 2010). Interestingly, the transcription of several transposable elements (i.e., putative RNA-directed DNA polymerases) was induced by a plant rhabdovirus or plant reovirus infection in their vector insects (plant/leafhoppers) (Martin et al, 2017). The current and previous studies (Lazareva et al, 2015) (Fig.…”
Section: Endogenization Of Virga/nege-like Viruses Into the Insect Gementioning
confidence: 64%
“…5 for bumblebee EVEs), suggesting that integrations might have occured due to non-homologous recombination between an RNA of the progenitor virus and that of a retrotransposon during reverse transcription of the retrotransposon (Ballinger et al, 2012;Geuking et al, 2009;Horie et al, 2010). Interestingly, the transcription of several transposable elements (i.e., putative RNA-directed DNA polymerases) was induced by a plant rhabdovirus or plant reovirus infection in their vector insects (plant/leafhoppers) (Martin et al, 2017). The current and previous studies (Lazareva et al, 2015) (Fig.…”
Section: Endogenization Of Virga/nege-like Viruses Into the Insect Gementioning
confidence: 64%
“…Thus, the virus can achieve the proliferation and cellular fitness by altering the host transcriptome responses, such as cellular responses associated with antiviral immunity and cell death/apoptosis. This remodeling effect of the virus on the host transcriptome is a common strategy exploited by the virus in hostvirus interactions and has been observed in various viruses [48][49][50]. Notably, a recent study showed that HSV-1 infection could not only result in changes in gene expression but also in alternative polyadenylation and splicing in the host transcriptome by influencing the host RNA processing [51].…”
Section: Discussionmentioning
confidence: 85%
“…In plants, the Barley yellow dwarf relies on the action of EIF4 for translation [53], as well as the human viruses Coxsackievirus [54] and Foot and Mouth virus [55]. Within insects EIF4 has been associated only with RNA Rhabdovirus and then in the negative sense of RNA Rhabdovirus [56]. Interestingly the role of EIF4 in honey bee RNA viruses has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%